RNA-Dependent DNA Polymerase Activity of RNA Tumor Viruses I. Directing Influence of DNA in the Reaction - Hurwitz, Jerard (1972)
The template requirements and deoxyribonucleic acid (DNA) products of the DNA polymerases isolated from Rauscher leukemia and avian myeloblastosis viruses have been examined. All DNA preparations or synthetic polydeoxynucleotides which are active as primers possess a duplex structure containing single-stranded regions with a 3′-hydroxyl terminus. Native DNA and fully single-stranded DNA are inactive; moreover, their activity is not enhanced by sonic oscillation or treatment with micrococcal nuclease, Neurospora nuclease, or low levels of deoxyribonuclease I. Poor DNA templates are activated by treatment with exonuclease III, large amounts of deoxyribonuclease I, or an endonuclease isolated from Rauscher viral preparations. In reactions primed with deoxyadenylate-deoxythymidylate copolymer, the product formed is covalently attached to primer strands, indicating that no new strands are initiated. DNA polymerase products formed with exonuclease III- or deoxyribonuclase I-treated DNA are duplex structures. Short single-stranded regions are completely filled in, whereas long single-stranded regions are only partly repaired. DNA preparations containing extensive single-stranded regions are poorly utilized as templates.